Biodegradation of Oil Contaminated Water by Filament Fungi (Texas Journal of Agriculture and Biological Sciences, 2022)
Twenty-two fungal isolates were isolated from five samples of oil-polluted water, the ability to grow on a solid mineral salt medium with 2% of crude oil was achieved; only seven isolates (WA2, WB3, WB7, WC2, WD3, WE2, and WE5) give clear-growing fungal colonies with different diameters. These fungal isolates are found to be more predominant in the polluted water samples, then they will be identified as Aspergillus fumigatus, Aspergillus niger, Trichoderma viridae, Fusarium verticelloides, penicillium oxysporum, Candida albicans, Aspergillus flavus respectively. In the present study, the primary and secondary screening of the ability of the isolates to degrade the crude oil was showed significant differences between the isolates on growth in the liquid medium containing 2% of crude oil and also in the percentage of crude oil biodegradation, while the isolate A. niger showed the highest ability compared with other studied isolates to consume the crude oil as carbon source with the best ratio of biodegradation reached to 95% after 28 days of incubation and the dry weight reached to 3.2 g after 7 days of incubation. Also, the results of GC showed the highest percentage loss of crude oil by A. niger which recorded 95% after 28 days of incubation, these results confirm the results of the screening tests for fungal isolates in terms of the similarity of the crude oil biodegradation rate after 7 days of incubation.